Gene Localization and Functional Validation of GmPDH1 in Soybean Against Cyst Nematode Race 4 - Yuehua Dai; Yue Zhang; Chuhui Li; Kun Wan; Yan Chen; Mengen Nie; Haiping Zhang (Plants)
To identify the key genes conferring resistance to soybean cyst nematode race 4 (SCN4, Heterodera glycines), this study utilized 280 recombinant inbred lines (RILs) derived from the resistant cultivar Huipizhiheidou (HPD) and the susceptible cultivar Jindou23 (JD23). Through phenotypic characterization and a genome-wide association study (GWAS), a genomic region (Gm18:1,223,546–1,782,241) on chromosome 18 was mapped, yielding 14 candidate genes. GmPDH1 was validated as a critical resistance gene using reverse transcription quantitative PCR (RT-qPCR) and Kompetitive Allele Specific PCR (KASP) marker M0526. RT-qPCR revealed that GmPDH1 expression in HPD roots was upregulated 9 days post-inoculation with SCN4 compared to uninoculated controls. KASP genotyping showed that marker M0526 efficiently distinguished between resistant and susceptible plants in natural populations: 71.05% of the resistant accessions exhibited resistant or moderately resistant genotypes, whereas 81.03% of the susceptible accessions showed susceptible or highly susceptible genotypes. Functional validation demonstrated that overexpression of GmPDH1 significantly enhanced SCN4 resistance in the susceptible cultivars JD23 and Jack, whereas CRISPR/Cas9-mediated knockout of GmPDH1 in HPD attenuated its resistance. This study confirmed GmPDH1 as a key gene governing SCN4 resistance and developed an efficient molecular marker, M0526, providing theoretical insights and technical tools for dissecting nematode resistance mechanisms and advancing soybean disease-resistant breeding.